Sugar and Fiber Content in Sorghum Seeds (Sorghum bicolor (L.) Moench) From the Application of Rice Husk Biochar and Liquid Cow Urine Organic Fertilizer - Syamsiar; Indrianto Kadekoh; Marhani; Maemunah; Rahmi Rozali; Rachmat Zainuddin; Nur Salam; Nina Humaerah (Postgraduate, University of Mataram, 2025)
Sorghum (Sorghum bicolor (L.) Moench) is a resilient cereal crop with high potential as a source of food, feed, and bioenergy. This study investigates the effect of applying rice husk biochar and liquid organic fertilizer (POC) from cow urine on the sugar and fiber content of sorghum seeds. The experiment was conducted in two phases: field trials using a randomized block design with nine treatment combinations (3 biochar doses × 3 POC doses) and laboratory analysis of sugar and fiber contents. Results show that the application of 4 t/ha biochar and 750 ml/L cow urine POC produced the highest yield in terms of seed weight per plot (0.36 t/ha) and total production. However, the highest sugar content (63.32%) was obtained in the control biochar treatment with 250 ml/L POC, suggesting that lower POC doses are more effective in enhancing sugar concentration. Fiber content showed no statistically significant differences among treatments, although a tendency for increased fiber was observed at moderate POC doses. These findings highlight the potential of using rice husk biochar and cow urine POC to improve sorghum productivity and nutritional quality while supporting sustainable and organic agricultural practices.